Ovarian clear cell carcinoma with or without endometriosis origin in a single institution cohort - Mingming Sun; Wei Jiang (Discover Oncology, 2023)
Abstract Background As ovarian clear cell carcinoma (OCCC) has distinct clinical features, biology, genetic characteristics and mechanisms of pathogenesis, and whether the origin of endometriosis or not affects the prognosis of OCCC remains controversial. Methods We retrospectively collected medical records and follow-up data of patients with OCCC treated at the Obstetrics and Gynecology Hospital of Fudan University from January 2009 to December 2019. Further, we divided patients into 2 groups. Group 1: non-endometriosis origin; Group 2: endometriosis origin. Clinicopathological characteristics and survival outcomes were compared between the 2 groups. Results A total of one hundred and twenty-five patients with ovarian clear cell carcinoma were identified and included. In the overall patients’ population, the 5 year overall survival was 84.8%, the mean overall survival was 85.9 months. The results of the stratified analysis showed that early stage (FIGO stage I/II) OCCC had a good prognosis. The results of univariate analyses indicated that a statistically significant relationship between overall survival (OS) and FIGO stage, lymph node metastasis, peritoneum metastasis, chemotherapy administration methods, Chinese herbal treatment, molecular target therapy. As for progression-free survival (PFS), a significant relationship between PFS and child-bearing history, largest residual tumor size, FIGO stage, tumor maximum diameter, lymph node metastasis was found, respectively. FIGO stage and lymph node metastasis are common poor prognostic factors affecting OS and PFS. The multivariate regression analysis revealed that FIGO stage (p = 0.028; HR, 1.944; 95% CI 1.073–3.52) and treatment by Chinese herbs (p = 0.018; HR, 0.141; 95% CI 0.028–0.716) were identified as influencing factors with regard to survival. The presence or absence of lymphadenectomy did not affect OS of 125 OCCC patients (p = 0.851; HR, 0.825; 95% CI 0.111–6.153). There was a trend towards a better prognosis for patients with OCCC of endometriosis origin than those with OCCC of non-endometriosis origin (p = 0.062; HR, 0.432; 95% CI 0.179–1.045). The two groups differed with respect to several clinicopathological factors. And the proportion of patients with disease relapse was higher in Group 1 (46.9%) than in Group 2 (25.0%), with a statistically significant difference (p = 0.048). Conclusions Surgical staging and treatment by Chinese herbs postoperatively are two independent prognostic factors affecting the OS of OCCC, early detection and Chinese herbal medicine combined with chemotherapy postoperatively may be a good choice. Tumor with endometriosis-origin was found less likely to relapse. While the non-necessity of lymphadenectomy in advanced ovarian cancer has been proven, the need for lymphadenectomy in the early stage ovarian cancer, including early stage OCCC, still deserved to be explored.